How multicultural counseling based on social capital in a plural society? - Rima Pratiwi Fadli; Herman Nirwana; Mudjiran Mudjiran (Indonesian Institute for Counseling, Education and Theraphy, 2023)
Social capital is directly linked to the phenomenon that occurs in the community. Multicultural counseling based on social capital can help with these issues. Social capital is a way of forming a strong link between people in order to establish a society. Social capital is divided into two categories: those that focus on the network of social contacts and those that focus on the inherent traits of individuals involved in social interactions. Multicultural counseling is still underserved in guidance and counseling services. One of the reasons why the service isn't up to par is because the counselor lacks certain talents, particularly when it comes to counseling approaches. As a result, a separate study on intercultural counseling is required. As a result, the author delivers a concept paper on multicultural counseling in a plural society in Indonesia based on social capital. After reviewing a variety of scientific sources, this manuscript was created. With this document, it is intended that counselors will be able to use it as a resource for implementing intercultural counseling based on social capital in Indonesia's plural society.